2020
DOI: 10.1108/itp-05-2019-0208
|View full text |Cite
|
Sign up to set email alerts
|

Building brand loyalty and endorsement with brand pages: integration of the lens of affordance and customer-dominant logic

Abstract: PurposeNumerous companies have launched brand pages (BPs) on social networking sites to enhance customer-brand communication, cultivate the customer-brand relationship and promote brand loyalty. This study aims to investigate how BP affordances support social commerce.Design/methodology/approachThe study devises a theoretical model linking the proposed BP affordances (visibility, selectivity, persistence and interactivity) to three customer values (relationship quality, brand experience and smart shopping feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 112 publications
(269 reference statements)
1
27
0
Order By: Relevance
“…The positive associations between three affordances and flow and the association between flow and problematic SVA use suggest a mediation model, in which flow mediates the relationship between three affordances and problematic SVA use, respectively. The mediating paths are in line with the S-O-R framework (Mehrabia and Russell, 1974;Fang et al, 2021;Tuncer, 2021), which assumes that certain affordances of a digital technology (e.g., recommendation algorithm, multimodality, and low-cost interaction) influence users' experiences in using this technology (e.g., flow), which in turn affects users' subsequent behaviors (e.g., problematic SVA use). Thus, we posit a set of hypotheses to test the mediating role of flow between three affordances and problematic SVA use: H5: Flow mediates the relationship between recommendation algorithm (H5.1), multimodality (H5.2), low-cost interaction (H5.3) and problematic SVA use, respectively.…”
Section: The Mediating Role Of Flowmentioning
confidence: 90%
See 2 more Smart Citations
“…The positive associations between three affordances and flow and the association between flow and problematic SVA use suggest a mediation model, in which flow mediates the relationship between three affordances and problematic SVA use, respectively. The mediating paths are in line with the S-O-R framework (Mehrabia and Russell, 1974;Fang et al, 2021;Tuncer, 2021), which assumes that certain affordances of a digital technology (e.g., recommendation algorithm, multimodality, and low-cost interaction) influence users' experiences in using this technology (e.g., flow), which in turn affects users' subsequent behaviors (e.g., problematic SVA use). Thus, we posit a set of hypotheses to test the mediating role of flow between three affordances and problematic SVA use: H5: Flow mediates the relationship between recommendation algorithm (H5.1), multimodality (H5.2), low-cost interaction (H5.3) and problematic SVA use, respectively.…”
Section: The Mediating Role Of Flowmentioning
confidence: 90%
“…Flow represents an immersive and optimal experience in which an individual gets fully absorbed in an activity and feels heightened enjoyment, curiosity, and little distinction between self and the environment (Csikszentmihalyi, 1990). According to the S-O-R framework in the digital environment (Fang et al, 2017(Fang et al, , 2021Tuncer, 2021), it is the setting and design of a technology that induces users' experience with the technology (Ghazali et al, 2018). Likewise, we assume that the technological affordances of SVAs are the antecedents that trigger users' flow experience.…”
Section: Technological a Ordances And Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated high-quality interactions help to alleviate interpersonal uncertainty and provide the foundation for attachment fortification between influencers and consumers (Aw and Labrecque, 2020;Jun and Yi, 2020;Thomson, 2006;Yuan and Lou, 2020). A handful of studies on consumer-brand relationships indirectly support this view by evidencing high interactivity in brand-consumers communication on social media as a driver to heightened relationship quality (Fang et al, 2021;Labrecque, 2014). Chung and Cho (2017) found that communicating directly with a celebrity through social media engenders a sense of personally knowing the celebrity.…”
Section: Interactivitymentioning
confidence: 99%
“…As the users spend more time on social network, this indicates more engaging activities when browsing and more likely to be interested in the brand's content (Chen & Tsai, 2020). As such, many brands and businesses have set up their own official brand/business page on social networking sites and utilise them as a platform connecting with potential and existing consumers (Jayasingh & Venkatesh, 2015;Fang, Li, & Bhatti, 2020).…”
Section: Introductionmentioning
confidence: 99%